2020
DOI: 10.1177/1534650120919797
|View full text |Cite
|
Sign up to set email alerts
|

Gender Conformity and Suicide: A Case Study Integrating Structural Family Therapy and Satir Experiential Therapy

Abstract: Recent studies have shown that suicidality among transgender youth are 3.6 times more likely to report suicidal ideation and 3.2 times more likely to attempt suicide compared with cisgender youth. To alleviate the suicide rates among transgender youth, research suggests the need for family-based interventions. This case study explores the integration of structural family therapy and the Satir growth model to increase connection and support within the family, while also creating clear boundaries that are protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…A few CFT models have been adapted to address suicidality. For example, Romney, Hawkins, and Soloski (2020) describe an integration of structural family therapy and experiential family therapy as a means of addressing suicidal ideation and behaviours in a gender non‐conforming adolescent. Additionally, Softas‐Nall and Francis (1998) introduce a solution‐focused approach to addressing suicidality.…”
Section: Relational Approaches To Addressing Suicidalitymentioning
confidence: 99%
“…A few CFT models have been adapted to address suicidality. For example, Romney, Hawkins, and Soloski (2020) describe an integration of structural family therapy and experiential family therapy as a means of addressing suicidal ideation and behaviours in a gender non‐conforming adolescent. Additionally, Softas‐Nall and Francis (1998) introduce a solution‐focused approach to addressing suicidality.…”
Section: Relational Approaches To Addressing Suicidalitymentioning
confidence: 99%
“…Leading researchers of affirmative practice have generally focused on group and family interventions with youth (e.g., Austin et al, 2016; Romney et al, 2020). In one study of a cognitive behavioral protocol, eight participants between the ages of 16 and 18 participated in an eight-module pilot study of AFFIRM, a transgender and nonbinary affirmative intervention (Austin et al, 2016).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…The researchers found that AFFIRM protocol significantly reduced depression scores and that reductions persisted past the 3-month follow-up survey (Austin et al, 2016). Other researchers have demonstrated, in more detailed, case-based scholarship, that family and systems-based interventions for transgender people are beneficial for transgender people (Romney et al, 2020).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%